Empowering inmates in Surabaya penitentiary to prevent tuberculosis through education and screening programs - Ramadhan, Roy Novri; Arini, Merita; Stephanie, Karyn; Saputra, Galang Nanda; Nugroho, Fajar Adi; Robbani, Ghulbuddin; Akram, Muh (Universitas Muhammadiyah Magelang, 2025)
Tuberculosis (TB) remains a significant public health issue, particularly in high-risk settings such as penitentiaries. This community service aimed to enhance TB awareness and management among inmates at the Surabaya penitentiary, East Java, Indonesia. The educational method employed was an interactive talk show, allowing participants to actively engage through question-and-answer sessions, discussions, and relevant case studies. This approach sought to improve participants' understanding and involvement, making the information more comprehensible and applicable to daily life. The program also included TB screening for inmates. Results showed a significant increase in participants' TB awareness. The percentage of participants able to correctly identify TB symptoms significantly improved, demonstrated by their ability to recognize common signs like prolonged cough, fatigue, and night sweats. Understanding of TB transmission also drastically increased, with 70% of participants realizing that TB spreads through airborne droplets when an infected person coughs or sneezes. Furthermore, awareness regarding TB prevention measures such as maintaining hygiene, mask usage, seeking early medical care, and adherence to treatment rose to 70%. These findings highlight the effectiveness of the educational program in reducing TB transmission and improving health within correctional facilities. Therefore, continuous implementation of similar programs in various penitentiaries is crucial for tackling TB in vulnerable populations and preventing its spread to the wider community.